Patients, Not Costs, Come First: Should Doctors Cut Costs at the Bedside? - Dyer, Allen R. (The Hastings Center report, 1986)
In their daily practices, can doctors be both patient advocates and society's agents in rationing costly care? Doctors disagree among themselves. Some argue that patients stand to benefit if doctors lead the movement for cost-effective care in hospitals, nursing homes, and patients' homes. For others cost-cutting at the bedside erodes the foundations of the doctor-patient relationship and compromises the quality of care.